Principles of security and trust : First international conference, POST 2012,held as part of the European joint conferences on theory and practice of software, ETAPS 2012, Tallinn, Estonia, March 24 - April 1, 2012, Proceedings - Guttman, Joshua D.; Degano, Pierpaolo (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the first International Conference on Principles of Security and Trust, POST 2012, held in Tallinn, Estonia, in March/April 2012, as part of ETAPS 2012, the European Joint Conferences on Theory and Practice of Software. The 20 papers, presented together with the abstract of an invited talk and a joint-ETAPS paper, were selected from a total of 67 submissions. Topics covered by the papers include: foundations of security, authentication, confidentiality, privacy and anonymity, authorization and trust, network security, protocols for security, language-based security, and quantitative security properties.